2021
DOI: 10.1097/j.pain.0000000000002399
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of distress regulation during preschool vaccinations: child and caregiver predictors

Abstract: Recent research has highlighted the need for a deeper understanding of the heterogeneity in trajectories of children's distress after acute pain exposure, moving beyond the group means of behavioural pain scores at a single timepoint. During preschool vaccinations, 3 distinct trajectories of postvaccination pain regulation have been elucidated, with approximately 75% of children displaying trajectories characterized by downregulation to no distress by 2 minutes postneedle and 25% concerningly failing to downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Clinically, children's quick regulation response immediately after the needle was inserted suggests children may require the greatest effort to regulate during the anticipatory period and may benefit the most from parent prompts to engage in coping behavior prior to needle insertion. This is in line with recent work on preschooler's distress regulation during vaccinations (Shiff et al., 2022). Our preliminary findings suggest that a brief mindfulness intervention may serve to dampen children's physiological arousal during and following venipuncture.…”
Section: Discussionsupporting
confidence: 91%
“…Clinically, children's quick regulation response immediately after the needle was inserted suggests children may require the greatest effort to regulate during the anticipatory period and may benefit the most from parent prompts to engage in coping behavior prior to needle insertion. This is in line with recent work on preschooler's distress regulation during vaccinations (Shiff et al., 2022). Our preliminary findings suggest that a brief mindfulness intervention may serve to dampen children's physiological arousal during and following venipuncture.…”
Section: Discussionsupporting
confidence: 91%
“…As hypothesized, greater distress pre-needle was associated with slower regulation across the vaccination appointment. This finding with pre-needle distress causing longer (Campbell et al, 2013;Lisi et al, 2013;Shiff et al, 2022). If a child is highly distressed pre-needle, it will likely impact not only their parents' behaviour, but their own ability to engage in autonomous self-regulation.…”
Section: The Role Of Pre-needle Distressmentioning
confidence: 92%
“…The path analysis generated in this paper demonstrated a complexity in caregiver behaviors such that coping-promoting behaviors are only predictive of lower pain , when caregivers are not also concurrently enacting distress-promoting behaviors . Most recently, Shiff et al 60 also examined the preschool-aged OUCH cohort wave and found that caregivers who engaged in higher coping-promoting behaviors 1 minute postneedle had children who were less regulated in their pain-related distress and responding, whereas those who engaged in higher coping-promoting behaviors 2 minutes postneedle had children who were more regulated. This suggests it is not just the behaviours themselves that are critical but the timing of these behaviours.…”
Section: Lesson 2: Managing Pain More About What One Should Not Do Th...mentioning
confidence: 99%
“…This pain domino effect has been wellreplicated with both younger and older waves of the OUCH Cohort. 12,31,60…”
Section: Anticipatory Distress and Pain Outcomes In Infantsmentioning
confidence: 99%
See 1 more Smart Citation